1983
DOI: 10.1038/jcbfm.1983.41
|View full text |Cite
|
Sign up to set email alerts
|

Global Cerebral Vasodilatation Elicited by Focal Electrical Stimulation within the Dorsal Medullary Reticular Formation in Anesthetized Rat

Abstract: Summary:We examined the effects of electrical stimu lation of a restricted area of the dorsal medullary reticular formation (DMRF) on regional cerebral blood flow (CBF) in anesthetized (by chloralose), paralyzed (by curare) rats. CBP was measured in tissue samples by the Kety prin ciple, with 14C-iodoantipyrine as indicator. Stimulation of DMRF elicited a widespread, significant increase in CBP in 12 of 13 areas. The increase in flow was greatest in cerebral cortex, up to 240% of control. However, it was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…The increases in rCBF were, with the exception of the cerebellum, bilateral and symmetrical and included also seg ments of brain from cortex to brain stem. These increases in rCBF cannot be attributed to effects of stimulation on blood gases since these were com parable in control and experimental animals; nor can the changes be attributed to the controlled hem orrhage since (a) removal of similar amounts of blood does not affect resting rCBF (Iadecola et al, 1983) and (b) electrical stimulation of the parabra chial nucleus of the pons, which requires approxi mately the same amount of hemorrhage, decreases rCBF (Mraovitch et al, 1985); nor can the changes in rCBF be attributed to a nonspecific effect of elec trical stimulation, since stimulation with identical parameters in an adjacent brain stem site failed to alter rCBF.…”
Section: Discussionmentioning
confidence: 99%
“…The increases in rCBF were, with the exception of the cerebellum, bilateral and symmetrical and included also seg ments of brain from cortex to brain stem. These increases in rCBF cannot be attributed to effects of stimulation on blood gases since these were com parable in control and experimental animals; nor can the changes be attributed to the controlled hem orrhage since (a) removal of similar amounts of blood does not affect resting rCBF (Iadecola et al, 1983) and (b) electrical stimulation of the parabra chial nucleus of the pons, which requires approxi mately the same amount of hemorrhage, decreases rCBF (Mraovitch et al, 1985); nor can the changes in rCBF be attributed to a nonspecific effect of elec trical stimulation, since stimulation with identical parameters in an adjacent brain stem site failed to alter rCBF.…”
Section: Discussionmentioning
confidence: 99%
“…Other changes that potentially could affect CBF during an episode of OSA include vasoactive substances in blood or stimulation of vasoactive central neurons. 93,94 In addition, the sensory, sympathetic, or parasympathetic nervous system innervates cerebral arteries 95 and could influence CBF during an episode of OSA. In general, however, activation of the sympathetic nervous system has little effect on the cerebral circulation except during some pathological states.…”
Section: Effects Of Osa On the Cerebral Circulationmentioning
confidence: 99%
“…(After Nakai et al 1983) There are several provocative studies that suggest activation of other brain areas is able to affect CBF directly. Reis and colleagues Iadecola et al 1982Iadecola et al , 1983 have found that electrical activations of distinct intrinsic pathways in the brain have substantial effects on CBF. Activation of the dorsal medullary reticular formation results in widespread increases in CBF with accompanying increases in cerebral metabolism (Iadecola et al , 1983.…”
Section: Central Pathwaysmentioning
confidence: 99%
“…Reis and colleagues Iadecola et al 1982Iadecola et al , 1983 have found that electrical activations of distinct intrinsic pathways in the brain have substantial effects on CBF. Activation of the dorsal medullary reticular formation results in widespread increases in CBF with accompanying increases in cerebral metabolism (Iadecola et al , 1983. In contrast, activation of the fastigial nucleus also causes widespread increases in CBF, but is unaccompanied by increases in cerebral metabolism ( Fig.…”
Section: Central Pathwaysmentioning
confidence: 99%